The Routledge encyclopedia of the Chinese language - Chan, Sin-wai; Li Wing Yee, Florence; Minett, James W. (Routledge, 2016)
"The Routledge Encyclopedia of the Chinese Language will truly meet the academic, linguistic and pedagogical needs of those who are interested in the Chinese language in different capacities and for different reasons, such as Sinologists, Chinese linguists, and teachers and learners of Chinese as a second language" -- Provided by publisher.